Abies jaliscana (Pinaceae): A new combination in section Grandis and a key to the species of Abies in western Mexico - Vazquez-García, J. Antonio; Shalisko, Viacheslav; Cuevas-Guzmán, Ramon; Muñiz-Castro, Miguel A.; Manilla-Blandón, Mauricio R. (Phytotaxa, 2014)
Recent morphological and phenological data support recognition of Abies jaliscana (Martínez) Mantilla, A. Vázquez & Shalisko at the species level. A key to distinguish A. jaliscana from other species of Abies in western Mexico is provided.